Group size and ranging patterns of Queen Elizabeth National Park elephants - Abe, Eve (Pachyderm, 1993)
Outlines results from an ongoing study focussing on the changes in group size and ranging patterns of elephants subsequent to the elimination of large scale poaching which took place in the area in the 1970s. Smaller groups are now more frequent and the groups are becoming more widely dispersed.